Fabricating continuous electroconductive polyacrylonitrile fibers with thermosensitive property via wet-spinning. (6th December 2017) - Liu, Wanwan; Jin, Yang; Wang, Yangyi; Ge, Mingqiao; Gao, Qiang
Abstract: In this work, conductive polyacrylonitrile (PAN) composite fiber with thermosensitive property was successfully prepared via wet-spinning. Thermochromic pigment (TCP) microsphere capsules were applied to manufacture color-changing fibers. Meanwhile, light-colored conductive whiskers (ATO@TiO2 ) were employed to endow polyacrylonitrile fibers with conductivity without prejudicing their thermosensitive property. Interestingly, unlike other conductive fibers in dark color, this kind of conductive composite fiber can be dyed by thermosensitive pigment. The obtained composite fiber containing 20 vol% ATO@TiO2 whiskers shows a resistivity of 10 5 Ω · cm and could generate heat by Joule heating when being applied under a certain voltage. The composite fiber shows a red color at room temperature, while the color of the composite fiber fades gradually and finally becomes white as temperature rise. This simple and cost-effective approach is expected to inspire more research into the applications of multifunctional conductive fibers.